Readings in business cycles - Gordon, Robert Aaron; Klein, Lawrence R.; American Economic Association (Homewood, illinois. : Published for the Association by R.D. Irwin inc., 1965)
The present volume is the second collection of reprints in the business cycle field to appear in this series. The first volume confined itself to business cycle theory. While this compilation readings in business cycles suggest the broader terms of reference that have guided the selection of articles for this volume. This book is on the simultaneous existence and mutual conditioning of economic growth and economic cycle.
Bibliographical footnotes.
oo 5/10/18
Loans
Keywords: Business cycles; Economic statistics; Econometric models; Forecasting